PENGARUH KESEPAKATAN ISTIMEWA TERHADAP KINERJA ANGGOTA DPRK BANDA ACEH DENGAN PERAN KELUARGA SEBAGAI MEDIASI DAN DUKUNGAN ORGANISASI SEBAGAI PEMEDIASI - M Arief Setia Budi; Said Musnadi; Syafruddin Chan (Jurnal Magister Manajemen, 2018)
The purpose of this study was to determine: (1) determine flexibility i – deals, family performance, performances of city council members Banda Aceh, and organizational support (2) influence of flexibility i – deals  and family performace to performances of city council members Banda Aceh (3) influence of the flexibility i – deals to family performace (3) family performace mediation influence flexibility i – deals to performances of city council members Banda Aceh(4) organizational support moderating influence flexibility i – deals to  performances of city council members Banda Aceh. The research was conducted in the Office City Council Members Banda Aceh with 30 member respondents. As the research object are flexibility i – deals, family performance, performances of city council members Banda Aceh, and organizational support. Results showed that flexibility i – deals  and family performace influence to performances of city council members Banda Aceh, there is influence flexibility i – deals to family performace, there is family performance mediation flexibility i – deals to performances of city council members Banda Aceh, and organizational support moderating influence flexibility i – deals to performances of city council members Banda Aceh.